Autophagy as a self-digestion signal in human cancers: Regulation by microRNAs in affecting carcinogenesis and therapy response. (March 2023) - Kadhim, Mustafa M.; Ramírez-Coronel, Andrés Alexis; Jalil, Abduladheem Turki; Talib, Hayder Abdullah; Gupta, Jitendra; Jawhar, Zanko Hassan; Saleh, Marwan Mahmood; Pandey, Vijay; Zhang, Xi; Khan, Haroon
Abstract: Autophagy is defined as a "self-digestion" signal, and it is a cell death mechanism its primary function is degrading toxic agents and aged organelles to ensure homeostasis in cells. The basic leve ls of autophagy are found in cells, and when its levels exceed to standard threshold, cell death induction is observed. Autophagy dysregulation in cancer has been well-documented, and regulation of this pathway by epigenetic factors, especially microRNAs (miRNAs), is interesting and noteworthy. miRNAs are considered short endogenous RNAs that do not encode functional proteins, and they are essential regulators of cell death pathways such as apoptosis, necroptosis, and autophagy. Accumulating data has revealed miRNA dysregulation (upregulation or downregulation) during tumor progression, and their therapeutic manipulation provides new insight into cancer therapy. miRNA/autophagy axis in human cancers has been investigated an exciting point is the dual function of both autophagy and miRNAs as oncogenic and onco-suppressor factors. The stimulation of pro-survival autophagy by miRNAs can increase the survival rate of tumor cells and mediates cancer metastasis via EMT inductionFurthermore, pro-death autophagy induction by miRNAs has a negative impact on the viability of tumor cells and decreases their survival rate. The miRNA/autophagy axis functions beyond regulating the growth and invasion of tumor cells, and they can also affect drug resistance and radio-resistance. These subjects are covered in the current review regarding the new updates provided by recent experiments. Graphical Abstract: ga1